A NOTE ON MEIOTIC CHROMOSOMES OF THE GIANT ACRIDID Eutropidacris collaris (STOLL) - Piza Jr., S. de Toledo (REVISTA DE AGRICULTURA, 2016)
A NOTE ON MEIOTIC CHROMOSOMES OF THE GIANT ACRIDID Eutropidacris collaris (STOLL)